A dynamic adaptive light field sampling approach for smart lighting control. (October 2014) - Dong, F; Sanderson, AC
Smart lighting is used to provide the right light to meet occupants' needs for efficiency, productivity and health. The development of adaptive control in smart lighting requires advanced real-time sensing technologies for monitoring the generated light field. This paper introduces a systematic approach to dynamic light field sampling using a distributed sensor network. A dynamic adaptive sampling algorithm is introduced to guide the adaptive selection and real-time reallocation of sample locations to track and estimate the generated light field and the daylight field. This approach generates a multi-scale functional representation of the light field, which can be an effective basis for lighting control. Experimental results have shown that a systematic dynamic selection of sensor locations can significantly reduce the error in representation of the light field with corresponding improvement in the lighting control.